Circular economy, motivations for its adoption, and the main challenges in its implementation “A presentation of the German experience (2017-2020)” - GUERROUAT Younes; ELKINAI Abdelhak; NOUI Noureddine (Journal of North African Economies, 2025)
This study aims to delve into understanding the nature of the circular economy, and its underlying principles, explore the motivations for transitioning towards it, and highlight the advantages and challenges hindering the shift. Additionally, this is done through using the descriptive approach and a case study method. The study concludes that the circular economy represents an alternative economic model to the linear economy, aiming to progress toward sustainability by maximizing product value, extending their lifespan, reducing waste and emissions, preserving the environment, and enhancing the efficiency of natural resource utilization. Furthermore, the study emphasizes that the German experience stands out as a leading example in the field of the circular economy, having embraced it since 1996 through the introduction of laws on the circular economy, waste management, and various legal frameworks enacted until 2019. Among its notable waste management strategies is the implementation of the waste hierarchy principle, aiming to separate economic growth from resource use.